Quality of pharmaceutical advertisements in medical journals: a systematic review - Othman, Noordin; Vitry, Agnes I.; Roughead, Elizabeth E. (The Public Library of Science (PLoS), 2009)
BACKGROUND: Journal advertising is one of the main sources of medicines information to doctors. Despite the availability of regulations and controls of drug promotion worldwide, information on medicines provided in journal advertising has been criticized in several studies for being of poor quality. However, no attempt has been made to systematically summarise this body of research. We designed this systematic review to assess all studies that have examined the quality of pharmaceutical advertisements for prescription products in medical and pharmacy journals.